1996
DOI: 10.1007/bf00366151
|View full text |Cite
|
Sign up to set email alerts
|

Ocular findings in children operated on for plagiocephaly and trigonocephaly

Abstract: Clinical examination of patients affected by plagiocephaly or trigonocephaly reveals evident malformation of the orbits, and the ocular repercussions are pronounced when children are operated on at an advanced age. Since it is generally accepted that binocular vision is fully developed by approximately 6 months of age, a late correction of plagiocephalic or trigonocephalic skull deformities may be an obstacle to the development of normal visual function. For the present report we investigated astigmatism and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 27 publications
2
51
1
Order By: Relevance
“…7 The underlying mechanism resulting in strabismus involves traction on the ocular globe induced by bone deformation caused by craniosynostosis. 6 Rekate 8 reports that strabismus, especially involving vertical eye movements, is common in the more severe forms of this disorder. A study by Fredrick et al 7 evaluated 13 patients with deformational plagiocephaly, of which 9 were found to have ipsilateral torticollis and 1 of these presented with strabismus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 The underlying mechanism resulting in strabismus involves traction on the ocular globe induced by bone deformation caused by craniosynostosis. 6 Rekate 8 reports that strabismus, especially involving vertical eye movements, is common in the more severe forms of this disorder. A study by Fredrick et al 7 evaluated 13 patients with deformational plagiocephaly, of which 9 were found to have ipsilateral torticollis and 1 of these presented with strabismus.…”
Section: Discussionmentioning
confidence: 99%
“…The need for early identification of strabismus is based on the development of binocular vision by ϳ6 months of age, whereby late correction may be an obstacle to the development of normal visual function. 6 History of strabismus of any type or need for ophthalmology evaluation was found in only 7 patients during the chart review. One of these 7 patients with plagiocephaly was part of the telephone interview, and only 1 sibling had a history of strabismus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Surgical management is indicated for two reasons. Growth restriction in the presence of a rapidly expanding growing brain may result in raised ICP, 7 and surgery may be indicated for the prevention or treatment of raised ICP.…”
Section: Nonsyndromic Craniosynostosesmentioning
confidence: 99%
“…Problems that arise in patients having positional plagiocephaly include craniofacial deformities as well as asymmetry of brain structures leading to eye and optic nerve asymmetry, strabismus, and visual acuity abnormalities. 12,18,40 Other reported complications are learning disability and delay in language development, as well as possible inhibition of psychosocial development as a result of the abnormal appearance. 19,27,35,40 …”
Section: Incidence and Adverse Effect Of Positional Plagiocephalymentioning
confidence: 99%